Pelarutan genangan cairan pencemaran yang melarut terbatas dalam air di dasar arus yang mengalir - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT Accidental spills of liquid material into hydrosphere can be classified into three main categories: soluble compounds that mix rapidly with the water, immiscible (insoluble or slightly soluble) compounds that float on the water, and immiscible compounds that sink to the bottom of the watercourse. This last category comprises 47 % of some 250 chemicals listed in the report to the EPA by Pilie et al. (1975). This study is concerned with the pool of soluble high-density immiscible chemical spills on water, as there is short of information on this phenomenom. The aim of this study is to determine the rate of solvation of immiscible chemical pools-water at the bottom. The experiment was carried out in the water bath provided with stirrer and plastic ripples at the bottom. Water was circulated by the circulation pump. The concentration of solute in the circulation tank was measured with cOnductivitymeter. Flow rate of water circulation and plastic ripples dimension were varied. Mathematical model suggested can be used to evaluate the interface mass transfer coefficien of immiscible chemical pools-water at the bottom of flowing streams. The Sherwood number for mass transfer has been obtained in the form: Sh = K' Re4 with the values of K' were 0.15